Pengaruh Kualitas Pelayanan, Nilai Pelanggan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Pada Pelanggan Taksi Konvensional (Studi Kasus pada Pelanggan Taksi Kosti Semarang) - Rachelia, Elisabeth Diandra; Widayanto, Widayanto (Jurnal Ilmu Administrasi Bisnis, 2018)
The competition taxi companies in Semarang city runs tightly, not onlyconventional taxies but also taxies online. Kosti taxi is one of the taxies affectedthis business competition. Sampling techniques use Purposive Sampling. Methodsof data analysis and testing use mediation analysis of Partial Least Square, namelythe WarpPLS 3.0. The test results direct influence of quality service , customer valueto the customer loyalty through customer satisfaction indicates a significantinfluence. Test results influence indirect of the variables also indicate a significantinfluence . The result of customer’s satisfaction as the pemediasi variable in themodel is partial mediation. Based on indicators that have the lowest value, theresearcher suggests to evaluate taxi driver service quality like to responsecustomer complain, pay attention to the accuracy of argo payments, increase socialcustomers value and improve the application of Kosti Taxi with add features attractcustomers.